2017
DOI: 10.1108/ijbm-09-2016-0137
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the effects of perceived values of mobile banking applications on customers

Abstract: Purpose The purpose of this paper is twofold: first, the authors empirically examine the effect of the perceived values of mobile banking (MB) applications on customers’ e-trust, e-satisfaction and e-loyalty and second, the authors investigate the moderating role of customers’ age in the relationship between perceived value of MB and e-trust. Design/methodology/approach A survey was conducted on a sample of 361 Tunisian banks’ customers using mobile applications. Structural equation modeling method was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
119
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(155 citation statements)
references
References 80 publications
(142 reference statements)
19
119
0
17
Order By: Relevance
“…Trust is associated with security/privacy and practicity (regarded as utilitarian factors), while commitment/satisfaction is driven by enjoyment and sociality (dimensions more hedonic by nature) Berraies et al (2017) To examine the effect of the perceived values of MB applications on customers' etrust, e-satisfaction and eloyalty Survey; Questionnaire; 361 MB consumers in Tunisia Quality, price and emotional perceived values' dimensions of MB applications are predictors of customers' e-trust. E-trust has positive effects on e-satisfaction and eloyalty.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…Trust is associated with security/privacy and practicity (regarded as utilitarian factors), while commitment/satisfaction is driven by enjoyment and sociality (dimensions more hedonic by nature) Berraies et al (2017) To examine the effect of the perceived values of MB applications on customers' etrust, e-satisfaction and eloyalty Survey; Questionnaire; 361 MB consumers in Tunisia Quality, price and emotional perceived values' dimensions of MB applications are predictors of customers' e-trust. E-trust has positive effects on e-satisfaction and eloyalty.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…It is also noticed further that 78% of wageearners around the world are without bank account, yet possess mobile phones, which is an indication of the huge market potential for Mobile Banking services (Muhammad Al Amine, 2016;World-Bank, 2018). The convenience of Mobile Banking has opened the avenue for banks to provide customers with the ability to virtually bank from anywhere and at any time, and to retain them (Baptista & Oliveira, 2017;Berraies, Yahia, & Hannachi, 2017). Again, banks through this channel are able to safeguard customers against competitors (Berraies et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dedeoglu, et al (2019) found that brand trust was affected positively by both hedonic and functional values. Berraies, et al (2017) found that customers' e-trust is explained by quality value, monetary value and emotional value of mobile banking applications. Moliner, et al (2007) concluded that the formation of customer trust is influenced by emotional value.…”
Section: Perceived Value and Customer Satisfactionmentioning
confidence: 99%